Temuan Variasi Bahasa Ragam Formal dan Informal dalam Serial Nurbaya dan Novel Sitti Nurbaya (Kajian Sosiolinguistik) - Nurkhairunisa, Sindi; Amin, Mujid Farihul (Wicara: Jurnal Sastra, Bahasa, dan Budaya, 2023)
The difference in the ages of the two objects in this study shows that there are differences in terms of the use of formal and informal language variations. This research uses descriptive qualitative method and the data of the research are obtained from the utterances in the dialogue of series Nurbaya and the novel Sitti Nurbaya. While the method of collecting data is documentary method with listening technique. The data are analyzed by Sociolinguistics theory and SPEAKING component technique. In the Nurbaya series, there are stories that show variations in formal and informal language. The variety of formal language in the Nurbaya series is marked by the background of the events that occurred; in the courtroom and workplace. The formal variety in the Nurbaya series can also be seen from the choice of the formal words such as Your Honor (Yang Mulia), brother (saudara), I (saya), you (anda), how (bagaimana), and Sir (tuan). The variety of formal languages in the Nurbaya series language variations are found in the form of Minang and Javanese dialects, idiolects from code mixing between Indonesian and Minang languages; Indonesian with Sundanese; and Indonesian with Betawi, sociolect in the form of slang and colloquial, and chronolect in the form of slang. The variety of formal language in Sitti Nurbaya's novel is characterized by the use of the greeting words engku and hamba. The data on the variety of informal languages in Sitti Nurbaya's novel is in the form of colloquial sociolect or language that use in a daily conversation and 1920s chronolect.Keywords: language variation, formal and informal language, sociolinguis